The impact of industry 4.0 adoption barriers on supply chain capacity and operational efficiency: Empirical evidence in Vietnamese transport logistics industry - Nhan Cam Tri (Global Business & Finance Review (GBFR), 2024)
Purpose: This study evaluates the impact of Industry 4.0 adoption on supply chain capacity and operational performance under the mediating effect of barriers at Vietnamese transport logistics companies. Design/methodology/approach: Based on the perspective of Contingency theory and Resource-based theory, the research model is proposed and data is surveyed from 768 managers at Vietnamese transport logistics companies. Data were processed using SPSS and AMOS software. Findings: The results show that internal and external barriers have a negative impact on Industry 4.0 adoption, supply chain capacity, and operational performance. Applying Industry 4.0 also increases the operational efficiency and capacity of the supply chain. Research limitations/implications: The study proposes some implications to help businesses in the industry apply Industry 4.0 more successfully. However, the research is limited in the scope of data samples. Specifically, the data sample in the study mainly focuses on transport and logistics businesses in Vietnam, reducing the representativeness and generalizability of the results. In addition, limitations in assessment methods need to be improved. Although using a linear structural model, the study still has limitations in accurately assessing the relationship between variables. Originality/value: The research has important implications for managers in successfully applying Industry 4.0 to increase supply chain capabilities and achieve operational efficiency.
Keywords: 650; Barriers; industry 4.0; Operational efficiency; Supply chain capacity; Transport logistics